Persepsi pengunjung apotek terhadap keamanan dan efektifitas obat tradisional di Kecamatan Paguyangan tahun 2021 - Efi Yulia Astuti; Aulia Rahman; Aziez Ismunandar (Prodi Farmasi Fakultas Sains dan Teknologi Universitas Peradaban, 2022)
Traditional medicine is an ingredient or concoction of ingredients derived from plants, animal materials, mineral materials or a mixture of these materials that are used for generations by the community as treatment. The use of traditional medicine is not only influenced by characteristics, it can also be influenced by perceptions. The purpose of this study was to determine the perception of pharmacy visitors and to determine the relationship between characterictics and perceptions of the safety and effectiveness of traditional medicines in Paguyangan District. This type of research is an observational study using cross sectional method. Sampling using accidental sampling method, with a total of 100 respondents who meet the inclusion and exclusion criteria. Perception was measured using a questionnaire with a Likert scale from strongly disagree to strongly agree (scale 1-5). Then converted to percent index score. Spearman correlation test was used to determine the relationship between respondents characteristics and perceptions of the safety and effectiveness of traditional medicines. The results of the study obtained that respondents were gender (53%), age 18-40 years (63%), high school education level (39%), level of self employment (45%), and income less than Rp. 2.000.000 (61%). The majority of respondents agree with the perception of the safety of traditional medicine, while the perception of the effectiveness of traditional medicine is still uncertain. There is a significant relationship between the type of work of the respondents with the perception of the safety of traditional medicine with a significance value of 0.007 (p< 0,05), and there is relationship between the type of work with the perception of the effectiveness of traditional medicine with a significance value of 0.002 (p< 0,05). Keyword :Pharmacy Visitor, Perception, traditional medicine